Effect of Application Intervals of Various Types of Insecticides in Controlling Fruit Fly (Bactrocera sp.) Pests on Production of Curly Red Chili (Capsicum annum L.) - Darmawansyah Darmawansyah; saripah ulpah; T. Edy Sabli (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
The study's full title was